Financial Efficiency of India Tourism Development Corporation (ITDC) Limited: An Empirical Study - Taqi, Mohd; Ajmal, Mohd; Ansari, Mohd Shamim (Journal of Tourism Management Research, 2018)
Tourism is one of the significant service sectors in India as it contributes about 9.6 per cent in Gross Domestic Production and the third largest foreign exchange earner for the country. The Government of India recognized this sector as an industry in 1986 and it became eligible for several incentives and facilities like tax incentives, subsidies etc. Further, the tourism industry was also declared as a priority sector for foreign investment in 1991. It is an important tool for employment generation, economic development and rural transformation. India is a country of vast geographical diversity which attracts tourists from all over the world throughout the year. A number of different groups, companies and organizations are operating in tourism sector like ITDC, Tata Group, Oberoi Group, ITC Ltd. etc. India Tourism Development Corporation (ITDC) is the leading public sector corporation and the prime mover in the progressive development, promotion and expansion of tourism in the country. Since, ITDC has been playing a vital role in the growth of tourism activities in the country, financial soundness and efficiency is prerequisite for such type of corporation engaged in development activities. Thus, it is important to investigate the operational activities and financial soundness of this corporation. The present study is an attempt to analyse the financial efficiency of ITDC in the context of its financial performance and operational activities from 2012-13 to 2016-17. The results indicated profitability and operational efficiency of this corporation found satisfactory during the study period. The study also concludes that ITDC is performing well in maintaining and developing tourism infrastructure and provide necessary facilities to the national and international tourist.